ISCHEMIRs: Finding a Way Through the Obstructed Cerebral Arteries - S. Nampoothiri, Sreekala; Vinayak Menon, Hari; Das, Debashish; Golgodu Krishnamurthy, Rajanikant (Current Drug Targets, 2016)
MicroRNAs (miRNAs) are small (19–25 nucleotides) non-coding single-stranded RNAs that control post-transcriptional gene expression. miRNAs are abundantly expressed in the brain, where they play key roles during neuronal differentiation, synaptogenesis, and plasticity. It is also becoming increasingly evident that miRNAs are involved in the etiology of several neurological disorders. Mounting evidence indicates that miRNAs have the ability to regulate the expression profiles of genes in signaling pathways associated with cerebrovascular diseases such as ischemic stroke, subarachnoid hemorrhage, and vascular dementia. For instance, miR-21 is involved in ischemic stroke pathology through atherosclerosis and provides neuroprotection by its anti-apoptotic features. miR-497 induces neuronal death and miR-210 is upregulated in hypoxic cells. Deregulated expression of miRNAs in response to ischemic stroke has enabled the use of miRNA as an efficient non-invasive biomarker. Antagomirs are often effective against neuronal apoptosis and can induce neuroregeneration following ischemia. Moreover, the advent of systems biology has introduced novel computational tools to identify the link between miRNAs, target genes and transcription factors involved in the stroke pathology and its treatment. This review describes the emerging role of miRNAs in neuroprotection and focuses on a subset of miRNAs that act as central players in ischemic stroke.
Keywords: microRNA